THE USAGE OF STRUCTURAL EQUATION MODELING (SEM) METHOD IN HYPERTENSION OCCURRING AT ACHMAD MOCHTAR HOSPITAL BUKITTINGGI - Abdi Iswahyudi Yasril; Wijayantono Wijayantono (Universitas Airlangga, 2022)
Hypertension or high blood pressure has many factors, the Structural Equation Modeling (SEM) method is able to analyze the multivariable and find out the direct and indirect effects in a model of the relationship among variables. The purpose of this research to determine the use of structural equation modeling methods (SEM) to assess the factors affecting hypertension in Achmad Mochtar Bukittinggi Hospital. This research is an observational analytic study with a cross-sectional design study. The research sample is 151 respondents at Poli Interne Ahmad Mochtar Bukittinggi Hospital. Analysis was with the structural equation modeling (SEM) method with a CI 95%. The results showed that of the 5 latent variables only 3 had a direct effect on hypertension, namely blood fat (T-value = 5.806), lifestyle (T-value = 13.505) and disease history (T-value = 2.518). )> 1.96. Meanwhile, demographics (0.530) and obesity (0.163) do not directly affect hypertension but can indirectly affect them. It can be concluded that: Lifestyle is a dominant factor because it can directly and indirectly affect hypertension through obesity, blood fats and disease history. It is expected that the research will be able to determine the problem solving plan of hypertension, because it will be known the model of the factors that influence the incidence of hypertension so that planning can be directed at variables that have a more significant influence